Huang’s three-step maneuver for laparoscopic spleen-preserving No. 10 lymph node dissection for advanced proximal gastric cancer - Huang, Chang-Ming; Chen, Qi-Yue; Lin, Jian-Xian; Zheng, Chao-Hui; Li, Ping; Xie, Jian-Wei (Chinese Journal of Cancer Research, 2014)
Due to the complexity of the splenic hilar vessels, their anatomical variation and the narrow and deep space, as well as the bleeding-prone splenic parenchyma and the difficulty to manage splenic or vascular bleeding at the splenic hilum,the procedure remains challenging and technically demanding procedure for the performance of laparoscopic pancreas- and spleen-preserving splenic hilar lymph nodes dissection. Based on our experiences, we gradually explored a set of procedural operation steps called “Huang’s three-step maneuver”. In this paper, we not only provide the concrete operation steps for the surgeon, but we also provide our recommended technique of pulling and exposure for assistants. This new maneuver simplifies the complicated procedure and improves the efficiency of laparoscopic spleen-preserving splenic hilar lymphadenectomy, making it easier to master and allowing for its widespread adoption.